Dilema Administrasi dan Agama: Implementasi SPTJM di Jantung Minangkabau (Studi Kasus Kecamatan Harau) - Susanti, Meria; Silvianetri, Silvianetri; Elimartati, Elimartati; Atsani, Ulya; Nofialdi, Nofialdi; Yunarti, Sri (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Unregistered marriages (nikah siri) remain a significant social phenomenon in the Minangkabau community, particularly in Harau District, Lima Puluh Kota Regency, West Sumatra. To address administrative barriers for children from these marriages, the government implemented the Absolute Statement of Responsibility (SPTJM) policy based on Minister of Home Affairs Regulation Numbers 108 and 109 of 2019, which allows for the inclusion of "Unregistered Marriage" status on Family Cards (Kartu Keluarga) and the issuance of complete birth certificates. This study analyzes the effectiveness of SPTJM implementation in Harau District and the dilemmas it raises from a maqasid sharia perspective, focusing on hifz al-nasl (protection of offspring) and hifz al-mal (protection of property). Using a qualitative juridical-empirical approach, data were collected through semi-structured interviews with couples using SPTJMs, those involved in unregistered marriages, employees of the Civil Registration Office (Disdukcapil), the Office of Religious Affairs (KUA), the Religious Court, and religious leaders, complemented by source and method triangulation. The research results show that the SPTJM effectively provides beneficial benefits in the form of quick and affordable access to children's administrative rights (identity, education, health, and social assistance), thus partially supporting hifz al-nasl. However, this policy creates more dominant long-term benefits, such as substantive legal uncertainty (difficulties in claiming inheritance and joint property), socio-customary conflicts (stigma and disputes over high inheritance rights in the Minangkabau matrilineal system), and a decline in interest in marriage confirmations, which weaken the obligation for official registration (Article 7 of the Compilation of Islamic Law). This article concludes that there is a dilemma between temporary administrative benefits and long-term damage to Islamic family law. The proposed recommendation is synergy between institutions (Disdukcapil, KUA, Religious Courts, and traditional leaders) through an affordable mass marriage confirmation program and outreach based on the maqasid sharia (Islamic principles) to maximize the necessities of life and minimize the mafsadah within the Minangkabau indigenous community.